The Progenitor Systems of Classical Novae in M31 - C. S. Abelson; Carles Badenes; Laura Chomiuk; Benjamin F. Williams; Katelyn Breivik; L. Galbany; C. Jiménez-Palau (The Astrophysical Journal)
We present the first characterization of the statistical relationship between a large sample of novae in M31 and their progenitor stellar populations in the form of a delay time distribution. To this end, we leverage the spatially resolved stellar age distribution of the M31 disk derived from deep Hubble Space Telescope photometry by the Panchromatic Hubble Andromeda Treasury survey and a large catalog of novae in M31. Our delay time distribution has two statistically significant detections: one population of nova progenitors with ages between 2 and 3.2 Gyr and an unnormalized rate of ( ${3.7}_{-3.5}^{+6.8}± 2.1)× {10}^{-9}$ events M _⊙ ^−1 , and another of ages between 7.9 Gyr and the age of the Universe with ( ${4.8}_{-0.9}^{+1.0}± 0.2)× {10}^{-9}$ events M _⊙ ^−1 (uncertainties are statistical and systematic, respectively). Together with the upper limits we derive at other time bins, these detections are consistent with either a constant production efficiency or a higher production efficiency of novae at earlier delay times.